Short-term quality of life change perceived by patients after transition to mandibular overdentures - Alessandra Julie SCHUSTER; Raissa Micaella MARCELLO-MACHADO; Amália Machado BIELEMANN; Gustavo Giacomelli NASCIMENTO; Luciana de Rezende PINTO; Altair Antoninha DEL BEL CURY; Fernanda FAOT (Sociedade Brasileira de Pesquisa Odontológica, 2017)
Abstract The aim of this longitudinal observational study was to evaluate the oral health-related quality of life (OHRQoL) following patient rehabilitation with implant-retained mandibular overdentures (IMO) and to identify the contribution of the different domains to OHRQoL. The Oral Health Impact Profile (OHIP-EDENT), Dental Impact on Daily Living (DIDL), and Geriatric Oral Health Assessment Index (GOHAI) questionnaires were completed twice by 25 patients: after 3 months of rehabilitation with complete dentures (CD) and after 3 months of IMO loading using stud abutments. The evaluation after IMO rehabilitation showed significant improvement in three DIDL domains: appearance (p = 0.011), eating and chewing (p = 0.003), and general performance (p = 0.003). The GOHAI results showed significant differences in two domains: psychosocial (p = 0.005) and pain and discomfort (p = 0.0004). The OHIP-EDENT outcomes showed significant improvements in five domains: functional limitation (p = 0.0001), physical pain (p = 0.0002), physical disability (p = 0.0010), and psychological disability and handicap (p = 0.032). The largest observed effect sizes were close to one standard deviation and were observed in the eating and chewing domain (0.93) of the DIDL; the pain and discomfort domain (0.83) of the GOHAI, and the functional limitation (0.89), physical pain (1.02), physical disability (0.84) domains of the OHIP-EDENT. The percentage of satisfied patients increased in all domains. Self-reported OHRQoL of CD wearers was significantly improved after 3 months of treatment with IMO, especially concerning the functional and pain-related aspects.